Design and Evaluation of Transdermal Patches of Labetalol Hydrochloride (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Î²-blockers like labetalol hydrochloride (LHCl) are potent and highly effective antihypertensiveagents. The main drawback associated with Î²-blockers is extensive first-pass metabolism, variable bioavailabilityrequiring frequent dose administration. This makes them an ideal candidate for transdermal therapeuticsystems. Î²-blockers formulated as transdermal therapeutic system should enhance the bioavailability as well asimprove patient compliance. Constant innovations and improvement in this field have potential that largeâ€scalecommercialization of transdermal dosage forms can be done. Aim: The aim of the present work was to develop andevaluate matrix type transdermal patches containing new polymeric combination to enhance the bioavailabilityas well as improve patient compliance. Materials and Methods: In present work development and evaluation ofmatrix-type transdermal patches containing a new polymeric combination of HPMC, carbopol934, ethyl cellulose,propylene glycol, polyethylene glycol, and isopropyl myristate for labetalol (LHCl) HCl (LBHCl). Film castingtechnique has been used in preparing patches. The patches were characterized for physical, in vitro release studiesand ex vivo permeation studies using human cadaver skin. Result: F6was found to be better than the otherformulations and hence selected as the optimized formulation on the basis of results of evaluating parameters suchas thickness, flatness, folding endurance, tensile strength, moisture content, moisture uptake, and drug content,formulation. The optimized patch was assessed for its pharmacokinetic, pharmacodynamic, skin irritation test andstability studies. Conclusion: Successful development of sustained release matrix type of transdermal patcheswhich can show greater patient compliance in treating hypertension has been done.